1978
DOI: 10.1038/bjc.1978.270
|View full text |Cite
|
Sign up to set email alerts
|

Differential arginine dependence and the selective cytotoxic effects of activated macrophages for malignant cells in vitro

Abstract: Summary.-Normal and neoplastic cells from 4 species (man, rat, mouse and hamster) were examined for their dependence on exogenous L-arginine in tissue culture. The malignant cells required a higher concentration of L-arginine in the medium than their normal counterparts (with similar doubling times) to maintain optimal proliferation. Complete arginine deprivation resulted in equal growth inhibition of normal and malignant cells, but more rapid cytolysis of the malignant cells. Deprivation of L-arginine, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1979
1979
1992
1992

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Furthermore, the experiments in which tumor cells are cocultivated with a mixture of tumor cells and effector cells, show that macrophage tumor cell contact is required for cytotoxicity to occur either aerobically or anaerobically (Table III). Therefore, despite the stress of anaerobic culture on the tumor cells, cytotoxicity is mediated by contact with BCG-macrophages, requires the same number of effector cells, and is not due to a nonspecific alteration of the medium (33,34).…”
Section: Amount Of Oxygen In the Anaerobicmentioning
confidence: 99%
“…Furthermore, the experiments in which tumor cells are cocultivated with a mixture of tumor cells and effector cells, show that macrophage tumor cell contact is required for cytotoxicity to occur either aerobically or anaerobically (Table III). Therefore, despite the stress of anaerobic culture on the tumor cells, cytotoxicity is mediated by contact with BCG-macrophages, requires the same number of effector cells, and is not due to a nonspecific alteration of the medium (33,34).…”
Section: Amount Of Oxygen In the Anaerobicmentioning
confidence: 99%
“…The major obstacles to further exploration of this approach are the very high Km of mammalian arginases and their very short half-life when injected. However, the selective cytotoxic effects of arginine deprivation previously reported (Currie & Basham, 1978) suggest that this or similar approaches to therapy may be worth further exploration. Dr Cifuentes was supported by the Fundacion Cien'tifica de la Associacion Espanola contra el Caincer.…”
Section: Discussionmentioning
confidence: 99%
“…One such product, arginase, is of interest to us since, as Kung et al (1977) have shown, induction of this enzyme in vitro may suppress T-cell function by depleting L-arginine from the culture medium. Furthermore, the selective in vitro cytotoxic activity of zymosan or lipopolysaccharide (LPS)-activated rodent macrophages for cultured malignant cells may be due to lethal deprivation of L-arginine mediated by arginase (Currie, 1978;Currie & Basham, 1978).…”
Section: Geneic L5178y Cellsmentioning
confidence: 99%
“…The diffusible mediators produced by macrophages that can affect target cells include reactive nitrogen intermediates [26,33], oxygen metabolites [44], arginase [5], neutral proteases [1,2], TNF [7,25,30,31], IL-1 [7,30,31,37,39,45], tumor cytotoxic factors [2,56], and complement breakdown products [8]. These diverse molecules are regulated by unique genes that are themselves induced by different signals.…”
Section: Activation Of Tumoricidal Properties In Mouse Macrophgesmentioning
confidence: 99%